Students Understanding of Earthquakes and Tsunamis in High Risk Areas - Cabello, Valeria M. (Frontiers in Earth Science, 2022)
Population growth and spread have increased human exposure to natural hazards and potential disasters affecting people's quality of life. This situation is especially manifested in marginalized or vulnerable areas. Moreover, within such vulnerable areas, children are affected, and are, at the same time, considered to be agents of change. However, children's voices have been scarcely considered for disaster risk reduction planning, and science education has not widely addressed these ideas. This study explores the understanding of earthquakes and tsunamis by children living in high-risk areas of Chile during a learning unit and according to their geographical zone. The study was part of a context-based science education learning unit. One hundred and two students from four schools used explanations to draw and write the causes of the risk situation, revealing their understanding of each phenomenon. The results show most students attributed earthquakes to the Tectonic Plates Theory while holding ancient scientific ideas about tsunami causes, for example, some explanations were based on air pressures. More sophisticated reasoning was found at the end of the learning unit, advancing their understanding of hazards promoted by the science education of the learning unit. The relevance of context-based science education for disaster risk reduction is discussed, especially for the cases of children with animistic - transferring human needs and attributes to non-animated entities- or fatalist understandings of the phenomena. The scientific understanding promotes empowerment and action-based choices for safety. Furthermore, the argument for policy curriculum design in primary science education for mitigating disasters is discussed.